Obliged to calculate: My School, markets, and equipping parents for calculativeness - Gobby, Brad (2015)
This paper argues neoliberal programs of government in education are equipping parents for calculativeness. Regimes of testing and the publication of these results and other organizational data are contributing to a public economy of numbers that increasingly oblige citizens to calculate. Using the notions of calculative and market devices, this paper examines the Australian Government’s My School website, which publishes academic and organizational information about schools, including national test results. While it is often assumed that such performance technologies contribute to neoliberal reform of education through school choice, the paper argues the website is technically limited in its capacity to facilitate the economic calculations and calculated action of parents resulting in school choice. The paper instead opens My School to analysis as a technique of governmental self-formation. Using the theoretical resources of actor-network theory and Foucauldian scholarship, this paper complicates assumptions in the literature about the extent to which My School actually operates as a ‘market mechanism’. It argues My School attempts to cultivate a calculated form of parental educational agency, irreducible to economic market agency.